New data on the systematics and distribution of snout moths of the genus Evergestis Hübner, [1825] in Kyrgyzstan (Lepidoptera: Crambidae) - Korb, Stanislav K.; Gorbunov, Pavel Yu.; Melyakh, Sergey F. (Zootaxa, 2024)
New data about distribution and systematics of snout moths of the genus Evergestis in Kyrgyzstan are presented. Evergestis radagastalis sp. n. is described, with the type locality: “Kyrgyzstan, Moldo-Too Mts., 7 km E of Kyzyl-Korgon, 41°43’43.08"N, 74°16’38.54"E, 1491 m”. It differs from the closely related species E. caesialis (Herrich-Schäffer, [1849]) and E. impervialis Sinev & Korb, 2021 by the wing pattern and genitalia structures. Evergestis grummi (Christoph, 1885) is recorded from Kyrgyzstan for the first time, Evergestis sorhageni (Sauber, 1899) is recorded for the first time from the Alai region, and Evergestis frumentalis (Linnaeus, 1761) is recorded for the first time from West Tian-Shan.